Pelatihan Pembelajaran Mendalam (Deep Learning) dengan Menggunakan Artificial Intelligence (AI) bagi Guru KKMA 02 Kabupaten Jepara - Ali Shodiqin; A B Prabowo K A; Sri Wahyuni; Muhammad Saifuddin Zuhri (Perkumpulan Kualitama Edukatika Indonesia, 2026)
Deep Learning is an instructional approach that promotes comprehensive understanding and the ability to connect learning materials with real-life contexts. This Community Service Program (PKM) aimed to provide theoretical and practical training, along with mentoring, for teachers of KKMA 02 Jepara Regency on implementing a deep learning approach supported by AI-based media. The program sought to enhance teachers’ theoretical understanding and practical skills in integrating AI tools, particularly ChatGPT and Wayground, into lesson planning and classroom practices. The workshop was conducted collaboratively using an andragogical approach. Training methods included lectures and discussions, demonstrations, and hands-on practice, with a composition of 25% theory and 75% practice. The program was held at Ono Joglo Resto, Jepara Regency. The activities focused on strengthening teachers’ cognitive competence in applying deep learning strategies, utilizing ChatGPT to support instruction, and employing Wayground for assessment and reflective learning. Following the workshop, participants were assigned to design lesson plans based on the deep learning approach integrated with AI-based media. The teachers demonstrated strong enthusiasm and reported that the training significantly supported and enriched their teaching practices through AI-assisted deep learning implementation.